Understanding India’s Initiatives towards Sustainable Development Goals: Through “SDG India Index”, with special reference to West Bengal’s Development (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In 2015, the United Nations General Assembly (UNGA) introduced the Sustainable Development Goals replacing the erstwhile Millennium Development Goals. SDGs also known as Global Goals which have 17 Goals and 169 targets, these are designed to transform the world while protecting the people and the planet at the same time. Majority of the targets are to be achieved by 2030, as set by the UNGA, although some have no end date. NITI Ayoga (abbreviation for National Institution for Transforming India) as the policy think tank of the Indian government every year released SDG India Index which justifies the developments at the national and sub-national levels towards achieving the Global Goals and Targets. The SDG Index is a useful technique to assess strength and weakness of the States/ UTs in terms of their performances to achieve SDGs and also encourages healthy competition. This paper will try to understand India’s as well as West Bengal’s initiatives and attainments towards SDGs through SDG India Index reports released till 2020-21 by NITI Ayoga. SDG Index reports released so far SDG Baseline Index 2018, SDG India Index 2019-20, SDG India Index 2020-21.The first ever SDG India Index of 2018 worked on 62 indicators consisting of 39 targets under 13 SDGS, the second SDG India Index of 2019 worked on 100 indicators consisting of 54 targets under17 SDGS. The recent SDG India Index of 2020-21 worked on 115 indicators covering 70 targets under 17 SDGs. Now less than ten years remains to attain the SDGs on its prescribed format by the UNGA. As the world’s largest democracy and one of the largest populated countries, India has more challenges in its way in order to achieve SDGs between this short time. The study tries to analyse the performance of West Bengal in terms of SDG India index reports.In this scenario SDG India Index Reports are not only remained as monitoring tool but also echoing the slogan of SDGs itself- “Leave No One Behind.” In this paper an attempt has been made to analyze the SDG India Index reports from 2018 to 2021. Here the study attempts to scrutinize the performance of West Bengal and India in terms of achievements made SDG attainment.